In foldl
, the combining function (or operator) associates to the left, meaning the left-most elements will be evaluated first, i.e. the most nested parentheses will be on the left side of the data structure. Therefore, its definition using recursion on lists would be:
foldl :: (a -> b -> a) -> a -> [b] -> a
foldl f v [] = v
foldl f v (x:xs) = foldl f (f v x) xs
So we take the second argument v
and the head of the list x
and apply the combining function on them, and then use that result to feed the recursive function for the rest of the list. The sum of a list using foldl
would be applied like this:
foldl (+) 0 [1, 2, 3]
foldl (+) (0 + 1) [2, 3]
foldl (+) ((0 + 1) + 2) [3]
foldl (+) (((0 + 1) + 2) + 3) []
(((0 + 1) + 2) + 3)
Notice that the places of the accumulator value v
are switched in foldl
relative to foldr
in the combining function f
. That is, in foldr
, the first argument of the combining function is an element from the data structure, while in foldl
, the first argument is the accumulator value and the second one is the element of the data structure. This may not be clear from the examples of sum
and product
, so let's implement a folding function that calculates the length of a list with both foldr
and foldl
using a lambda function as the combining function:
lengthr :: [a] -> Int
lengthr = foldr (\_ n -> n + 1) 0 -- list element first, accumulator second
ghci> lengthr [1, 2, 3]
3
If we want to declare the same function with foldl
, we have to reverse the arguments for the combining function to avoid a type error:
lengthl :: [a] -> Int
lengthl = foldl (\n _ -> n + 1) 0 -- accumulator first, list element second
Prelude> lengthl [1, 2, 3]
3